INCOMBUSTIBLE DECORATIVE SHEET - OKAMOTO MASAYASU; UKON FUMINORI; UOZUMI TAKAO (2019)
To provide an incombustible decorative sheet that suppresses blooming and color tone change while reducing a gross calorific value.SOLUTION: The present invention provides an incombustible decorative sheet in which a top film layer, an ink layer, a base film layer, and an adhesive layer are stacked in this order. The top film layer and the base film layer contain a polyvinyl chloride resin. The base film layer contains a bromine flame retardant 0-15 pts.wt. and antimony trioxide 0-10 pts.wt. relative to the polyvinyl chloride resin 100 pts.wt. The adhesive layer contains the bromine flame retardant 2-15 pts.wt. and the antimony trioxide 2-15 pts.wt. relative to an adhesive 100 pts.wt. The top film layer does not contain the bromine flame retardant or the antimony trioxide.SELECTED DRAWING: Figure 1 【課題】総発熱量を低減しつつ、ブルームの発生及び色調変化を抑制した不燃性化粧シートを提供する。【解決手段】トップフィルム層、インキ層、ベースフィルム層、及び、粘着剤層の順に積層され、上記トップフィルム層及び上記ベースフィルム層は、塩化ビニル樹脂を含有し、上記ベースフィルム層は、上記塩化ビニル樹脂１００重量部に対して、臭素系難燃剤を０〜１５重量部、三酸化アンチモンを０〜１０重量部含有し、上記粘着剤層は、粘着剤１００重量部に対して、上記臭素系難燃剤を２〜１５重量部、上記三酸化アンチモンを２〜１５重量部含有し、上記トップフィルム層は、上記臭素系難燃剤及び上記三酸化アンチモンを含有しない不燃性化粧シート。【選択図】 図１